The dynamics of data packet in transmission session - Abubakar Ibrahim, Adamu; Elnour Mohamed, Elbaraa Eldaw; M.Khedher, Akram M. Zeki (IEEE, 2017)
This paper presents a coordinated framework of prepared data packet transmission in a transmission session. Automated guided vehicles (AGVs) with an onboard 1-km range APC transmitter are used to establish the network environment for testing the prepared packet transmission session. An evaluation technique of the dataow through the network was carried out. The captured transmission parameters offer an inbound and outbound limit of dataow through which the AGVs communicate with each other. The ndings of this paper indicate that the ideal transmission rates at the frequency of 434 MHz and at a baud rate of 19200 bps was found to be 25 ms in between each 56-B data packets. The range of distance between the transmitter and the receiver was 0.5 to 970 m. The transmitter had a 1-km range limitation. As the applications for which the communication model was developed did not require long distances, the transmitter's range limitation was sufcient. Further tests validated these transmission session parameters values. The proposed techniques can be implemented as logistic and automation solutions in the manufacturing industry